Old Times on the Upper Mississippi : Recollections of a Steamboat Pilot from 1854 to 1863 - Merrick, George Byron (Fesler-Lampert Minnesota heritage book series., 2014)
George Byron Merrick chronicles the entire panorama of steamboat life he experienced in the mid-1800s, where he started as a cabin boy and worked up to cub pilot on the mighty Mississippi. Originally published in 1909, Merrick's narrative matches lively stories about gamblers, shipwrecks, and steamboat races with rich descriptions of river life and steamboat operations. George Byron Merrick (1841-1931) grew up in Prescott, Wisconsin, at the junction of the Mississippi and St. Croix rivers. After nine years of steamboating, he volunteered for the Wisconsin Infantry during the Civil War before settling into life as a newspaper editor and publisher.